Method for producing monolith compacted alumina material for single crystal growth
By using micron-level high-purity alumina particles mixed with solvent to form a slurry in the sapphire industry and drying them in the casting mold, the problems of low density and high impurities of alumina materials in the prior art are solved, and efficient and low-cost alumina materials production are achieved.
Patent Information
- Application Number
- CN202380055382.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-20
- Filing Date
- 2023-06-16
- Publication Date
- 2025-03-07
AI Technical Summary
The prior art faces problems of low bulk density and high impurity content when producing alumina materials used in the sapphire industry, resulting in low efficiency and capacity of sapphire furnaces and high cost and operational challenges in the production process.
By mixing micron-scale high-purity alumina particles with solvent to form a slurry and drying in a casting mold, high-density compacted alumina green and monoliths are obtained, mechanical compaction steps are avoided, and operating costs and impurities are reduced.
The high density of alumina materials (2.0g/cm3 to 3.7g/cm3) and low impurity content are achieved, reducing the operational challenges and costs of the production process and improving the efficiency and capacity of the sapphire furnace.
Smart Images

Figure CN119585225A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Patent Application No. 63 / 353,834, filed on June 20, 2022. This document is incorporated herein by reference in its entirety. Technical Field
[0003] The present application relates to the field of producing alumina. More specifically, the present application relates to a method for producing compacted alumina material. Background Art
[0004] Alumina (Al2O3) is one of the most commonly used ceramic materials in the advanced ceramics industry. Alumina is extracted from bauxite using the Bayer process. The material is suitable for many applications in various industrial, technological and military uses due to its high thermal, electrical and physical properties. Today, alumina is used in several modern industries such as synthetic sapphire, light emitting diodes (LEDs), semiconductors and lithium-ion batteries (LIBs), automotive and aerospace industries, wear protection, dental and orthopedic implants.
[0005] One specific application is the single crystal growth industry, such as synthetic sapphire. For sapphire production, high purity alumina (HPA) is required, which is mostly obtained by calcining aluminum salts. Such aluminum salts can be, but are not limited to, aluminum chloride, aluminum nitrate, aluminum sulfate, ammonium aluminum sulfate and ammonium aluminum hydroxide carbonate, or hydrates thereof; organic aluminum salts such as aluminum oxalate, aluminum acetate, aluminum stearate, aluminum lactate and aluminum laurate.
[0006] The main disadvantage of aluminum oxide from aluminum salts used in the sapphire industry is its low bulk density, which reduces the efficiency and capacity of sapphire furnaces. For example, aluminum oxide from aluminum chloride hexahydrate has a bulk density of about 0.4 g / cm 3 The loose bulk density is the true density of alumina (3.96 g / cm 3 ). The cycle time for sapphire production is about 3 weeks, which includes heating to the melting temperature of alumina (>2000°C) and then controlled cooling under vacuum. Therefore, if a low-density feed (such as alumina from aluminum chloride) is used in such a furnace, only 10% of the furnace capacity is used. In addition, the low density is a sign of porosity, which can absorb large amounts of gases (such as oxygen, water vapor), which cause bubbles and other defects in the crystal and also significantly reduce the life of the crucible, heating elements and other parts of the crystal growth furnace.
[0007] Therefore, HPA powders must be pre-treated in a way that significantly increases their density and reduces the amount of trapped gas. For higher efficiency in a sapphire furnace, the feed alumina is usually compacted and sintered before feeding into the sapphire furnace. Compacting produces a green body with acceptable strength, and sintering increases the density of the green body. Generally speaking, for single crystal growth, a density above 3.2 g / cm is required. 3 Some of the main methods of compaction / forming of ceramic powders are freeze casting, slip casting, powder injection molding, cold isostatic pressing, uniaxial molding, extrusion additive manufacturing.
[0008] The flow chart presented in FIG1 illustrates a method typically used to produce compacted materials for the sapphire industry. Commercially, these compacted materials are called "pucks". Generally speaking, the feed HPA powder has a large particle size, and compacting / sintering such large particles is not feasible. Therefore, the HPA particles should pass through a grinding step. The typical grinding technique is wet grinding, in which the powder is ground using ceramic grinding media. The product of the wet mill is a slurry of alumina, which should be dried. The typical equipment for drying the alumina slurry is a spray dryer. In most cases, an organic binder is added to the slurry to enhance the mechanical strength of the green body after the compaction step. The binder is used because α-alumina is not easy to agglomerate. Many sapphire manufacturers have encountered problems when using binders to achieve compacted materials. This organic binder is usually burned during the sintering process, but it is also possible that the binder is trapped in closed pores, which increases the impurity content of the material. Small amounts of impurities (ppm level) can affect the quality of the resulting single crystals and cause the crystals to be opaque. Therefore, more and more suppliers are developing water-based slurries for sintering processes. In general, few suppliers can provide high density (>3.2g / cm 3 , binder-free material with high purity).
[0009] The operation of a spray dryer presents challenges and it is difficult to dry the powder without forming agglomerates. The formation of agglomerates often affects the quality of the compaction step. Compaction is usually performed under high pressure using a uniaxial press to form a green body. The pressure required is high (10,000 psi to 50,000 psi). There are several disadvantages to using such a press:
[0010] High cost of automatic equipment or low production capacity of manual equipment.
[0011] HPA has poor flowability, which makes the use of automatic feeding of alumina powder not feasible or reliable. Therefore, manual feeding is used, which affects productivity.
[0012] The material of the die and punch in the press can be made of tool steel, and this material can increase the impurity content of the HPA powder, especially considering that aluminum oxide is an abrasive. Another option for the die and punch material is ceramic (e.g. carbide), in which case fine HPA powder can flow into the gap between the die and punch and may damage the part.
[0013] During the compaction process of alumina, alumina powder tends to stick to the punch or die. To solve this problem, lubricants can be used on the surface of the die and punch, but this also increases the impurities of the powder.
[0014] Due to the high pressures required to compact the HPA powder into a green body, higher forces are required to produce larger discs, and most molds cannot withstand very high loads, which may lead to mold cracking. This mainly happens with rectangular molds, where high stresses exist in the corners of the mold. To reduce stress, cylindrical molds can be used, but this is not preferred because it reduces the capacity of the sapphire furnace to π / 4.
[0015] The compacted materials produced have limited shapes and limited sizes. The compacted materials should then be strategically placed inside the furnace for single crystal growth to optimize space. Furthermore, when placed inside the furnace, when the furnace is not square or rectangular, there are gaps between the compacted materials, which reduces the efficiency / capacity of the furnace.
[0016] In KR20130022616A, it has been proposed to produce larger compacted materials, but this technique still uses a pressing step which increases the chance of cross contamination and involves higher capital and operating costs, as explained above. In addition, pressing the alumina particles pushes the particles in a random orientation, which preserves the gaps between the particles. Therefore, the green density obtained by this method is 1.9 g / cm 3 Up to 2.4g / cm 3 Furthermore, a maximum amount of water can be used in this process. Therefore, the ground material needs to be spray dried in order to prepare the slurry, so a spray drying step is still involved.
[0017]
[0006] Therefore, there is a need to provide improved methods for preparing compacted alumina that overcome at least some of the disadvantages of existing methods. Summary of the invention
[0018] It has been surprisingly shown herein that compacted alumina monoliths can be produced according to the methods of the present application, providing larger monoliths with higher density suitable for the single crystal growth industry, such as synthetic sapphire. Thus, the methods of the present application provide for the production of compacted monoliths with reduced impurity content, while also reducing operational challenges and costs. The present application also provides the use of these methods for producing compacted alumina monoliths, and the monoliths obtained thereby. Comparable methods do not show the same properties, highlighting the surprising results obtained using the methods of the present application.
[0019] Therefore, the present application includes a method for producing a compacted alumina green body, the method comprising: pouring a slurry into a casting mold, the slurry comprising micron-sized high-purity alumina particles and a solvent; and drying the slurry to obtain the compacted alumina green body.
[0020] In some embodiments, the high purity alumina is selected from alpha alumina, transition alumina, amorphous alumina and mixtures thereof, or the high purity alumina is doped with at least one element selected from Mg, Ba, Si, Ti, Zr, Fe, W, Zn and rare earth elements, or the high purity alumina is a mixture of high purity alumina and metal oxides.
[0021] In some embodiments, the method further comprises grinding the high purity alumina to obtain micron-sized particles. In some embodiments, the grinding is performed in a wet mill, a dry mill, a ball mill, an air jet mill, or a steam jet mill.
[0022] In some embodiments, the micron-sized high-purity alumina particles have a particle size distribution of about 0.5 microns to about 100 microns. In some embodiments, the micron-sized high-purity alumina particles have a particle size distribution of about 0.5 microns to about 50 microns. In some embodiments, the micron-sized high-purity alumina particles have a particle size distribution of about 1 micron to about 5 microns.
[0023] In some embodiments, the amount of solvent is about 5 wt % to about 75 wt % based on the total weight of the slurry. In some embodiments, the amount of solvent is about 10 wt % to about 40 wt % based on the total weight of the slurry. In some embodiments, the amount of solvent is about 10 wt % to about 20 wt % based on the total weight of the slurry.
[0024] In some embodiments, the slurry is obtained by mixing high purity alumina and a solvent. In some embodiments, the solvent is selected from water, methanol, ethanol, isopropanol, acetone and mixtures thereof. In some embodiments, the solvent is water.
[0025] In some embodiments, the slurry further comprises an organic binder, a dispersant, or a mixture thereof. In some embodiments, the organic binder is a polymer selected from the group consisting of carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyethylene glycol (PEG). In some embodiments, the dispersant is selected from the group consisting of 4,5-dihydroxy-1,3-benzenedisulfonic acid disodium salt, carbonate, ammonium polymethacrylate, carbonate, sodium pyrophosphate, diammonium hydrogen citrate, triammonium salt of aurintricarboxylic acid, Darvan CN, sodium pyrophosphate, diammonium hydrogen citrate, citric acid, nitric acid, ascorbic acid, ammonium polyacrylate, and polycarbonate.
[0026] In some embodiments, the method also includes a settling period before drying the slurry to allow the micron-sized particles to settle. In some embodiments, the settling period also includes a vibrating mold. In some embodiments, the settling period is carried out for about 0.5 hours to about 24 hours. In some embodiments, the settling period is carried out for about 1 hour to about 12 hours. In some embodiments, the settling period is carried out for about 1 hour to about 5 hours.
[0027] In some embodiments, drying is performed in an oven, a gas combustion dryer, an electric dryer, or a microwave oven. In some embodiments, drying is performed at a temperature of about 15°C to about 150°C. In some embodiments, drying comprises heating at a temperature of about 30°C to about 150°C. In some embodiments, drying comprises heating at a temperature of about 50°C to about 150°C.
[0028] In some embodiments, drying is performed for about 0.5 hours to about 1 week. In some embodiments, drying is performed for about 1 hour to about 48 hours. In some embodiments, drying is performed for about 12 hours to about 24 hours.
[0029] In some embodiments, the method further comprises removing the compacted alumina green body from the casting mold and subjecting the compacted alumina green body to heat treatment, thereby providing a single integrally compacted alumina sheet. In some embodiments, the heat treatment comprises heating at a temperature of about 150°C to about 1200°C. In some embodiments, the heat treatment comprises heating at a temperature of about 200°C to about 1200°C. In some embodiments, the heat treatment comprises heating at a temperature of about 250°C to about 1200°C. In some embodiments, the heat treatment is performed for about 0.5 hours to about 24 hours. In some embodiments, the heat treatment is performed for about 1 hour to about 12 hours. In some embodiments, the heat treatment is performed for about 2 hours to about 5 hours.
[0030] In some embodiments, the method further comprises removing the compacted alumina green body from the casting mold and subjecting the compacted alumina green body to sintering, thereby providing a single integrally compacted alumina sheet. In some embodiments, sintering comprises heating at a temperature of about 1200°C to about 1800°C. In some embodiments, sintering comprises heating at a temperature of about 1400°C to about 1800°C. In some embodiments, sintering comprises heating at a temperature of about 1600°C to about 1800°C. In some embodiments, sintering is performed for about 0.5 hours to about 24 hours. In some embodiments, sintering is performed for about 2 hours to about 12 hours. In some embodiments, sintering is performed for about 2 hours to about 8 hours.
[0031] In some embodiments, the casting mold is made of foam plastics, polytetrafluoroethylene (PTFE), silicone polymer, polystyrene. In some embodiments, the casting mold has a rectangular shape, a square shape, is circular or oval. In some embodiments, the casting mold has a thickness of about 50mm to about 200mm. In some embodiments, the casting mold has a thickness of about 100mm to about 200mm. In some embodiments, the casting mold has a thickness of about 100mm to about 150mm.
[0032] In some embodiments, the compacted alumina green body has a mass of about 2.0 g / cm 3 To about 3.3g / cm 3 In some embodiments, the compacted alumina green body has a bulk density of about 2.3 g / cm 3 To about 3.0g / cm 3 In some embodiments, the compacted alumina green body has a bulk density of about 2.5 g / cm 3 To about 2.8g / cm 3 The bulk density.
[0033] In some embodiments, a single integrally compacted alumina sheet has a mass of about 3.0 g / cm 3 To about 3.7g / cm 3 In some embodiments, a single integrally compacted alumina sheet has a bulk density of about 3.1 g / cm 3 To about 3.6g / cm 3 In some embodiments, a single integrally compacted alumina sheet has a bulk density of about 3.2 g / cm 3 To about 3.5g / cm 3 The bulk density.
[0034] In some embodiments, the method does not comprise a mechanical compaction step.
[0035] A compacted alumina green body produced by the method of the present application is also provided.
[0036] The present application also includes a compacted alumina green body comprising compacted micron-sized high-purity alumina particles.
[0037] Also provided is a single integrally compacted alumina sheet produced by the method of the present application.
[0038] The present application also includes a single integrally compacted alumina sheet comprising compacted micron-sized high purity alumina particles.
[0039] In some embodiments, the compacted alumina green body and the single integral compacted alumina sheet have the properties as defined above.
[0040] Also included is the use of the alumina green body or a single integrally compacted alumina sheet of the present application in a single crystal growth process.
[0041] Also provided is the use of the alumina green body or a single integrally compacted alumina sheet of the present application in a single crystal growth furnace.
[0042] Also included is the use of the alumina green body or a single integrally compacted alumina sheet of the present application in sapphire production.
[0043] Other features and advantages of the present application will become apparent from the following specific embodiments. However, it should be understood that although the detailed description and specific examples show the embodiments of the present application, they are only given in an illustrative manner, and the scope of the claims should not be limited to these embodiments, but should be given the broadest interpretation consistent with the description as a whole. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Embodiments of the present application will now be described in more detail with reference to the accompanying drawings, in which:
[0045] FIG. 1 shows a flow chart of a representative method of the prior art.
[0046] Figure 2 A flow chart of a method of the present application is shown according to an exemplary embodiment.
[0047] Figure 3 An image of an exemplary compacted alumina green body (Example 1) obtained by the method of the present application, according to an exemplary embodiment, is shown.
[0048] Figure 4 An image of an exemplary compacted alumina monolith (Example 1) obtained by the method of the present application, according to an exemplary embodiment, is shown.
[0049] Figure 5 An image of an exemplary compacted alumina green body (Example 2) obtained by the method of the present application, according to an exemplary embodiment, is shown. DETAILED DESCRIPTION
[0050] I. Definitions
[0051] Unless otherwise indicated, the definitions and embodiments described in this section and elsewhere are intended to apply to all embodiments and aspects of the application described herein to which they apply as would be understood by one skilled in the art.
[0052] As used in this application and claims, the words "comprises" (and any forms of including, such as "includes" and "containing"), "has" (and any forms of having, such as "holding" and "having"), "includes" (and any forms of containing, such as "including" and "containing"), or "containing" (and any forms of containing, such as "including" and "including") are inclusive or open-ended, and do not exclude additional, unrecited elements or method steps.
[0053] As used herein, the term "consisting of" and its derivatives are intended to serve as closed terms that specify the presence of stated features, elements, components, groups, integers and / or steps, and also exclude the presence of other unstated features, elements, components, groups, integers and / or steps.
[0054] As used herein, the term "consisting essentially of" is intended to specify the presence of stated features, elements, components, groups, integers, and / or steps as well as those that do not materially affect the essential and novel characteristics of these features, elements, components, groups, integers, and / or steps.
[0055] As used herein, the terms "about", "substantially" and "approximately" mean a reasonable amount of deviation of the modified term such that the end result is not significantly changed. These degree terms should be interpreted as including at least ±5% deviation of the modified term in the case where the deviation does not negate the meaning of the word it modifies, unless the context suggests otherwise to a person skilled in the art.
[0056] As used in this application, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise.
[0057] In embodiments comprising an "additional" or "second" component, the second component as used herein is chemically different from the other components or the first component. The "third" component is different from the other components, the first component and the second component, and further listed or "additional" components are similarly different.
[0058] As used herein, the term "and / or" means that the listed items are present or used alone or in combination. In fact, the term means "at least one" or "one or more" of the listed items are used or present.
[0059] As used herein, the term "suitable" means that the selection of specific compositions or conditions will depend on the specific step to be performed, the nature of the components to be converted and / or the specific use of the composition, but such selection will be well within the skills of one skilled in the art.
[0060] As used herein, the term "smelter grade alumina" or "SGA" refers to a grade of alumina that can be used in a process for preparing aluminum alloys. Smelter grade alumina typically contains α-Al2O3 in an amount less than about 5 wt%, based on the total weight of the smelter grade alumina.
[0061] As used herein, the term "high purity alumina" or "HPA" refers to an alumina grade containing alumina in an amount of 99 wt% or greater, based on the total weight of the high purity alumina.
[0062] As used herein, the expression "transitional alumina" refers to a polymorphic form of alumina other than α-alumina. For example, the transitional alumina may be χ-Al2O3, κ-Al2O3, γ-Al2O3, θ-Al2O3, δ-Al2O3, η-Al2O3, ρ-Al2O3, or a combination thereof.
[0063] As used herein, the expression "amorphous alumina" refers to a non-crystalline polymorph of aluminum oxide that lacks the long-range order characteristic of crystals.
[0064] As used herein, the term "sintering" generally refers to the thermal process of converting loose, fine particles into a solid, coherent mass by applying heat and, optionally, pressure without completely melting the particles to a melting point.
[0065] As used herein, the term "single crystal growth" generally refers to the growth of a bulk inorganic single crystal, which is a solid in which the crystal lattice throughout the sample is continuous and unbroken to the edges of the sample, having no grain boundaries.
[0066] As used herein, in the context of alumina, the term "green" refers to a block of material that typically requires further processing (eg, by firing, sintering, etc.) prior to use.
[0067] As used herein, in the context of alumina, the term "monolith" refers to a single, large, organized mass, and may also be referred to interchangeably as a single integrally compacted sheet of alumina.
[0068] As used herein, the terms "kiln," "furnace," and "oven" are used interchangeably and refer to an insulated chamber that produces temperatures sufficient to accomplish a process of converting a material into another form or a chemically different material, such as by hardening, drying, calcining, etc.
[0069] II. Methods and Uses of the Present Application
[0070] It has been surprisingly shown herein that compacted alumina monoliths can be produced according to the methods of the present application, providing larger monoliths with higher density suitable for the single crystal growth industry, such as synthetic sapphire. Thus, the methods of the present application provide for the production of compacted monoliths with reduced impurity content, while also reducing operational challenges and costs. The present application also provides the use of these methods for producing compacted alumina monoliths, and the monoliths obtained thereby. Comparable methods do not show the same properties, highlighting the surprising results obtained using the methods of the present application.
[0071] Therefore, the present application includes a method for producing a compacted alumina green body, the method comprising: pouring a slurry into a casting mold, the slurry comprising micron-sized high-purity alumina particles and a solvent; and drying the slurry to obtain the compacted alumina green body.
[0072] In some embodiments, the high purity alumina (HPA) is selected from alpha-alumina, transition alumina, amorphous alumina, and mixtures thereof. In some embodiments, the HPA is doped with at least one element, or is a mixture of HPA and other metal oxides. In some embodiments, the dopant is selected from Mg, Ba, Si, Ti, Zr, Fe, W, Zn, and rare earth elements. Those skilled in the art will appreciate that the composition of the starting material may be varied depending on the intended use of the final compacted material.
[0073] In some embodiments, the solvent is selected from water, methanol, ethanol, isopropanol, acetone, and mixtures thereof. In some embodiments, the solvent is water.
[0074] In some embodiments, the method further comprises grinding the high purity alumina to obtain micron-sized particles. In some embodiments, the grinding is carried out in a wet mill, a dry mill, a ball mill, an air jet mill, a steam jet mill, etc. It will be within the ability of a skilled person to select appropriate techniques and equipment to grind the material to a suitable size.
[0075] In some embodiments, the micron-sized high-purity alumina particles have a particle size distribution of about 0.5 microns to about 100 microns. In some embodiments, the micron-sized high-purity alumina particles have a particle size distribution of about 0.5 microns to about 50 microns. In some embodiments, the micron-sized high-purity alumina particles have a particle size distribution of about 1 micron to about 5 microns.
[0076] In some embodiments, the amount of solvent is about 5 wt % to about 75 wt % based on the total weight of the slurry. In some embodiments, the amount of solvent is about 10 wt % to about 40 wt % based on the total weight of the slurry. In some embodiments, the amount of solvent is about 10 wt % to about 20 wt % based on the total weight of the slurry.
[0077] In some embodiments, the slurry is obtained by mixing high purity alumina and a solvent.
[0078] In some embodiments, the slurry further comprises an organic binder, a dispersant, or a mixture thereof. In some embodiments, the organic binder is a polymer selected from the group consisting of carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA), and polyethylene glycol (PEG). In some embodiments, the dispersant is selected from the group consisting of 4,5-dihydroxy-1,3-benzenedisulfonic acid disodium salt (Tiron TM ), carbonate (Dolapix TM CE 64), ammonium polymethacrylate (Darvan TM C), carbonate (Dolapix ET 85), sodium pyrophosphate, diammonium hydrogen citrate, triammonium salt of aurintricarboxylic acid (Aluminon TM ), Darvan CN, sodium pyrophosphate, diammonium hydrogen citrate, citric acid, nitric acid, ascorbic acid, ammonium polyacrylate (Seruna TM D-305) and polycarbonate (Dolapix PC33). In some embodiments, the method is binder-free.
[0079] In some embodiments, the method also includes a settling period before drying the slurry to allow the micron-sized particles to settle. In some embodiments, the settling period also includes a vibrating mold. In some embodiments, the settling period is carried out for about 0.5 hours to about 24 hours. In some embodiments, the settling period is carried out for about 1 hour to about 12 hours. In some embodiments, the settling period is carried out for about 1 hour to about 5 hours.
[0080] In some embodiments, drying is carried out in an oven, a gas combustion dryer, an electric dryer, or a microwave oven. In some embodiments, drying is carried out at a temperature of about 15°C to about 150°C. In some embodiments, drying includes heating at a temperature of about 30°C to about 150°C. In some embodiments, drying includes heating at a temperature of about 50°C to about 150°C. In some embodiments, drying is carried out for about 0.5 hours to about 1 week. In some embodiments, drying is carried out for about 1 hour to about 48 hours. In some embodiments, drying is carried out for about 12 hours to about 24 hours.
[0081] In some embodiments, the method further comprises removing the compacted alumina green body from the casting mold and subjecting the compacted alumina green body to heat treatment, thereby providing a single integrally compacted alumina sheet. In some embodiments, wherein the heat treatment comprises heating at a temperature of about 150°C to about 1200°C. In some embodiments, the heat treatment comprises heating at a temperature of about 200°C to about 1200°C. In some embodiments, the heat treatment comprises heating at a temperature of about 250°C to about 1200°C. In some embodiments, the heat treatment is performed for about 0.5 hours to about 24 hours. In some embodiments, the heat treatment is performed for about 1 hour to about 12 hours. In some embodiments, the heat treatment is performed for about 2 hours to about 5 hours.
[0082] In some embodiments, the method further comprises removing the compacted alumina green body from the casting mold and subjecting the compacted alumina green body to sintering, thereby providing a single integrally compacted alumina sheet. In some embodiments, sintering comprises heating at a temperature of about 1200°C to about 1800°C. In some embodiments, sintering comprises heating at a temperature of about 1400°C to about 1800°C. In some embodiments, sintering comprises heating at a temperature of about 1600°C to about 1800°C. In some embodiments, sintering is performed for about 0.5 hours to about 24 hours. In some embodiments, sintering is performed for about 2 hours to about 12 hours. In some embodiments, sintering is performed for about 2 hours to about 8 hours.
[0083] In some embodiments, the mold is made of foam plastic, Styrofoam TM , polytetrafluoroethylene (PTFE-Teflon TM ), silicon polymer, polystyrene. In some embodiments, the casting mold has a rectangular shape, a square shape, is circular, oval, etc. In some embodiments, the casting mold has a thickness of about 50mm to about 200mm. In some embodiments, the casting mold has a thickness of about 100mm to about 200mm. In some embodiments, the casting mold has a thickness of about 100mm to about 150mm. Those skilled in the art will readily appreciate that the size and shape of the mold can be easily adjusted according to the desired final product and its use.
[0084] In some embodiments, the compacted alumina green body has a mass of about 2.0 g / cm 3 To about 3.3g / cm 3 In some embodiments, the compacted alumina green body has a bulk density of about 2.3 g / cm 3 To about 3.0g / cm 3 In some embodiments, the compacted alumina green body has a bulk density of about 2.5 g / cm 3 To about 2.8g / cm3 The bulk density.
[0085] In some embodiments, the compacted alumina monolith (single unitary piece), i.e., after heat treatment / sintering, has a density of about 3.0 g / cm 3 To about 3.7g / cm 3 In some embodiments, the compacted alumina green body has a bulk density of about 3.1 g / cm 3 To about 3.6g / cm 3 In some embodiments, the compacted alumina green body has a bulk density of about 3.2 g / cm 3 To about 3.5g / cm 3 The bulk density.
[0086] In some embodiments, the method does not comprise a mechanical compaction step.
[0087] The present application also provides a compacted alumina green body and a single integrally compacted alumina sheet produced by the method of the present application.
[0088] Also included are alumina green bodies or single integrally compacted alumina sheets comprising compacted micron-sized high purity alumina particles.
[0089] In some embodiments, the compacted alumina green body and the single integral compacted alumina sheet will have the shape and size of the casting mold as defined above. In addition, those skilled in the art will readily appreciate that the size and shape of the mold can be easily adjusted to provide the compacted alumina green body and the single integral compacted alumina sheet of the desired size and shape according to the desired use.
[0090] The present application also provides the use of a compacted alumina green body and a single integral compacted alumina sheet for single crystal growth.
[0091] The present application also provides the use of the compacted alumina green body and a single integrally compacted alumina sheet in a single crystal growth furnace.
[0092] In some embodiments, the method of the present application can be used to produce compacted materials as feed for the synthetic sapphire industry. Major applications of sapphire are, for example, but not limited to, wafers for semiconductors and camera lenses, jewelry, medical, defense, aviation, watches, display covers, and LEDs.
[0093] Example
[0094] The following non-limiting examples are illustrative of the present application.
[0095] General approach
[0096] A flow chart of the method of the present application is shown in Figure 2 In the process of preparing the alumina powder, the feed (HPA powder) is ground in a wet mill to produce a micron-sized powder. The output of the grinder is a slurry of alumina. Optionally, the feed may already be micron-sized and the grinding step may be omitted. In this case, deionized water may be added to the alumina powder in an amount of 10% to 30% by weight to prepare a slurry. The slurry is then cast / poured into a mold. Before drying, the cast material is left undisturbed for several hours to allow time for the alumina particles to settle (settling period). Without being bound by theory, during this step, the alumina particles settle in an organized manner to minimize the gaps between the particles and maximize the green density. When the settling of the material is completed, excess water may optionally be removed from the surface of the settled portion. The mold is then placed in an oven to remove additional free water and dry the slurry. The oven temperature may vary between room temperature and 150°C. When the free water evaporates, the green material is removed from the mold, and the green density is between 2.0 g / cm 3 Up to 2.8g / cm 3 For some applications of single crystal growth operations, the green body can be used as is. Optionally, further heat treatment, such as sintering, can be performed.
[0097] Example 1
[0098] 4.00 kg of micron-grade high-purity alumina (99.999%) derived from the decomposition of aluminum chloride hexahydrate was mixed with deionized water to produce an alumina slurry. The concentration of water in the slurry was 20% by weight. The slurry was poured into a rectangular Styrofoam 195 mm x 145 mm tumbler. TM The material was placed in a laboratory environment overnight (settling period). It was then dried in an oven at about 80°C. The material was removed from the mold and its green density was >2.6 g / cm 3 ,like Figure 3 The block was then sintered at 1600°C for 5 hours. Figure 4 As shown, and its density is 3.3g / cm 3 .
[0099] Example 2
[0100] Micron-sized high purity alpha alumina (99.999%) derived from the decomposition of aluminum chloride hexahydrate was mixed with deionized water to produce an alumina slurry. The concentration of water in the slurry was 15 wt%. The slurry was poured into a cylindrical Styrofoam mold with a diameter of 241.3 mm. The material was left overnight in a laboratory environment (settling period). It was then dried in an oven at 70°C to 80°C for 48 hours. The material was removed from the mold and Figure 5The density is shown as 2.639 g / cm 3 The green body was then sintered at about 1600°C for about 5 hours to obtain a density of 3.2 g / cm 3 , a monolith with a height of 86.9 mm and a diameter of 212 mm to 218 mm.
[0101] result
[0102] As shown in the above examples, the method of the present application produces a monolithic compacted material that can be assembled in the crucible of a single crystal growth furnace. Compared with the commonly used method of producing small rectangular compacted materials, the gaps between the compacted materials are reduced, and therefore more material can be loaded into the furnace. This method of the present application provides a simple, reliable, flexible, cost-effective and pollutant-free method.
[0103] Depending on the shape and size of the single crystal growth furnace, the compacted material can be produced in any shape and any size, whereas conventional methods are only able to produce small rectangular shapes.
[0104] The method of the present application also eliminates the uniaxial compaction step, reducing capital and operating costs, and avoiding cross contamination of dies and punches from the press.
[0105] The method of the present application also replaces the complicated spray drying step with conventional drying, which also reduces capital and operating costs.
[0106] Since the addition of organic binder is also optional during the application process, potential contamination from the binder can be avoided, not to mention the advantage of avoiding the cost of purchasing high-purity binder.
[0107] Finally, the green body obtained has a very high density (2.7 g / cm 3 Up to 2.8g / cm 3 ), which can be used directly in a single crystal growth furnace, thus avoiding the need for expensive and high-maintenance sintering furnaces.
[0108] Although the applicant's teachings described herein are in conjunction with various embodiments for illustrative purposes, it is not intended that the applicant's teachings be limited to these embodiments, as the embodiments described herein are intended to be examples. Rather, the applicant's teachings described and illustrated herein encompass various alternatives, modifications, and equivalents without departing from the embodiments described herein, the general scope of which is defined in the appended claims.
Claims
1. A method for producing a compacted alumina green body, the method comprising: pouring a slurry into a casting mold, the slurry comprising micron-sized high-purity alumina particles and a solvent; as well as The slurry is dried to obtain the compacted alumina green body.
2. The method according to claim 1, wherein the high purity alumina is selected from alpha alumina, transition alumina, amorphous alumina and mixtures thereof, or the high purity alumina is doped with at least one element selected from Mg, Ba, Si, Ti, Zr, Fe, W, Zn and rare earth elements, or the high purity alumina is a mixture of high purity alumina and metal oxides. 3 . The method according to claim 1 , further comprising grinding the high purity alumina to obtain the micron-sized particles.
4. The method according to claim 3, wherein the grinding is carried out in a wet mill, a dry mill, a ball mill, an air jet mill or a steam jet mill.
5. The method of any one of claims 1 to 4, wherein the micron-sized high purity alumina particles have a particle size distribution of about 0.5 microns to about 100 microns.
6. The method of any one of claims 1 to 4, wherein the micron-sized high purity alumina particles have a particle size distribution of about 0.5 microns to about 50 microns.
7. The method of any one of claims 1 to 4, wherein the micron-sized high purity alumina particles have a particle size distribution of about 1 micron to about 5 microns.
8. The method according to any one of claims 1 to 7, wherein the amount of the solvent is from about 5 wt% to about 75 wt% based on the total weight of the slurry.
9. The method according to any one of claims 1 to 7, wherein the amount of the solvent is from about 10 wt% to about 40 wt% based on the total weight of the slurry.
10. The method according to any one of claims 1 to 7, wherein the amount of the solvent is from about 10 wt% to about 20 wt% based on the total weight of the slurry.
11. The method according to any one of claims 1 to 10, wherein the slurry is obtained by mixing the high-purity alumina and the solvent.
12. The method according to any one of claims 1 to 10, wherein the solvent is selected from water, methanol, ethanol, isopropanol, acetone and mixtures thereof.
13. The method according to any one of claims 1 to 10, wherein the solvent is water.
14. The method according to any one of claims 1 to 13, wherein the slurry further comprises an organic binder, a dispersant or a mixture thereof.
15. The method according to claim 14, wherein the organic binder is a polymer selected from carboxymethyl cellulose (CMC), polyvinyl alcohol (PVA) and polyethylene glycol (PEG).
16. The method according to claim 14, wherein the dispersant is selected from the group consisting of 4,5-dihydroxy-1,3-benzenedisulfonic acid disodium salt, carbonates, ammonium polymethacrylate, carbonates, sodium pyrophosphate, diammonium hydrogen citrate, triammonium salt of aurintricarboxylic acid, Darvan CN, sodium pyrophosphate, diammonium hydrogen citrate, citric acid, nitric acid, ascorbic acid, ammonium polyacrylate and polycarbonates.
17. The method of any one of claims 1 to 16, further comprising a settling period prior to drying the slurry to allow the micron-sized particles to settle.
18. The method of claim 17, wherein the settling period further comprises vibrating the mold.
19. The method of claim 17 or 18, wherein the settling period is performed for about 0.5 hours to about 24 hours.
20. The method of claim 17 or 18, wherein the settling period is carried out for about 1 hour to about 12 hours.
21. The method of claim 17 or 18, wherein the settling period is performed for about 1 hour to about 5 hours.
22. The method according to any one of claims 1 to 21, wherein the drying is carried out in an oven, a gas combustion dryer, an electric dryer or a microwave oven.
23. The method of any one of claims 1 to 22, wherein the drying is performed at a temperature of about 15°C to about 150°C.
24. The method of any one of claims 1 to 22, wherein the drying comprises heating at a temperature of about 30°C to about 150°C.
25. The method of any one of claims 1 to 22, wherein the drying comprises heating at a temperature of about 50°C to about 150°C.
26. The method of any one of claims 1 to 25, wherein the drying is performed for about 0.5 hours to about 1 week.
27. The method of any one of claims 1 to 25, wherein the drying is performed for about 1 hour to about 48 hours.
28. The method of any one of claims 1 to 25, wherein the drying is performed for about 12 hours to about 24 hours.
29. The method of any one of claims 1 to 28, further comprising removing the compacted alumina green body from the casting mold and subjecting the compacted alumina green body to heat treatment to provide a single integral compacted alumina sheet.
30. The method of claim 29, wherein the thermal treatment comprises heating at a temperature of about 150°C to about 1200°C.
31. The method of claim 29, wherein the thermal treatment comprises heating at a temperature of about 200°C to about 1200°C.
32. The method of claim 29, wherein the thermal treatment comprises heating at a temperature of about 250°C to about 1200°C.
33. The method of any one of claims 29 to 32, wherein the heat treatment is performed for about 0.5 hours to about 24 hours.
34. The method of any one of claims 29 to 32, wherein the heat treatment is performed for about 1 hour to about 12 hours.
35. The method of any one of claims 29 to 32, wherein the heat treatment is performed for about 2 hours to about 5 hours.
36. The method of any one of claims 1 to 28, further comprising removing the compacted alumina green body from the casting mold and subjecting the compacted alumina green body to sintering to provide a single integral compacted alumina sheet.
37. The method of claim 36, wherein the sintering comprises heating at a temperature of about 1200°C to about 1800°C.
38. The method of claim 36, wherein the sintering comprises heating at a temperature of about 1400°C to about 1800°C.
39. The method of claim 36, wherein the sintering comprises heating at a temperature of about 1600°C to about 1800°C.
40. The method of any one of claims 36 to 39, wherein the sintering is performed for about 0.5 hours to about 24 hours.
41. The method of any one of claims 36 to 39, wherein the sintering is performed for about 2 hours to about 12 hours.
42. The method of any one of claims 36 to 39, wherein the sintering is performed for about 2 hours to about 8 hours.
43. The method according to any one of claims 1 to 42, wherein the casting mold is made of foam plastic, Styrofoam TM , polytetrafluoroethylene (PTFE), silicone polymer, and polystyrene.
44. The method according to any one of claims 1 to 43, wherein the casting mold has a rectangular shape, a square shape, is circular or oval.
45. The method of any one of claims 1 to 44, wherein the casting mold has a thickness of about 50 mm to about 200 mm.
46. The method of any one of claims 1 to 44, wherein the casting mold has a thickness of about 100 mm to about 200 mm.
47. The method of any one of claims 1 to 44, wherein the casting mold has a thickness of about 100 mm to about 150 mm.
48. The method of any one of claims 1 to 47, wherein the compacted alumina green body has a density of about 2.0 g / cm 3 To about 3.3g / cm 3 The bulk density.
49. The method of any one of claims 1 to 47, wherein the compacted alumina green body has a density of about 2.3 g / cm 3 To about 3.0g / cm 3 The bulk density.
50. The method of any one of claims 1 to 47, wherein the compacted alumina green body has a density of about 2.5 g / cm 3 To about 2.8g / cm 3 The bulk density.
51. The method of any one of claims 29 to 42, wherein the single integrally compacted alumina sheet has a g / cm 3 To about 3.7g / cm 3 The bulk density.
52. The method of any one of claims 29 to 42, wherein the single integrally compacted alumina sheet has a thickness of about 3.1 g / cm 3 To about 3.6g / cm 3 The bulk density.
53. The method of any one of claims 29 to 42, wherein the single integrally compacted alumina sheet has a thickness of about 3.2 g / cm 3 To about 3.5g / cm 3 The bulk density.
54. The method according to any one of claims 1 to 53, which does not comprise a mechanical compaction step.
55. The method of any one of claims 1 to 13, which is binder-free.
56. A compacted alumina green body produced by the method of any one of claims 1 to 28.
57. A compacted alumina green body comprising compacted micron-sized high purity alumina particles.
58. The compacted alumina green body of claim 56 or 57, the compacted alumina green body having a density of about 2.0 g / cm 3 To about 3.3g / cm 3 The bulk density.
59. The compacted alumina green body of claim 56 or 57, the compacted alumina green body having a density of about 2.3 g / cm 3 To about 3.0g / cm 3 The bulk density.
60. The compacted alumina green body of claim 56 or 57, the compacted alumina green body having a density of about 2.5 g / cm 3 To about 2.8g / cm 3 The bulk density.
61. The compacted alumina green body of any one of claims 56 to 60, having a rectangular shape, a square shape, a circular shape, or an oval shape.
62. The compacted alumina green body of any one of claims 56 to 60, having a thickness of about 50 mm to about 200 mm.
63. The compacted alumina green body of any one of claims 56 to 60, having a thickness of about 100 mm to about 200 mm.
64. The compacted alumina green body of any one of claims 56 to 60, having a thickness of about 100 mm to about 150 mm.
65. The compacted alumina green body of any one of claims 56 to 64, being binder-free.
66. A single integrally compacted alumina sheet produced by the method of any one of claims 29 to 42.
67. A single integrally compacted alumina sheet comprising compacted micron-sized high purity alumina particles.
68. The single integrally compacted alumina sheet of claim 66 or 67, having a density of about 3.0 g / cm 3 To about 3.7g / cm 3 The bulk density.
69. The single integrally compacted alumina sheet of claim 66 or 67, having a density of about 3.1 g / cm 3 To about 3.6g / cm 3 The bulk density.
70. The single integrally compacted alumina sheet of claim 66 or 67, having a density of about 3.2 g / cm 3 To about 3.5g / cm 3 The bulk density.
71. The single integrally compacted alumina sheet of any one of claims 66 to 70, having a rectangular shape, a square shape, a circular shape, or an oval shape.
72. The single integrally compacted alumina sheet of any one of claims 66 to 70, having a thickness of about 50 mm to about 200 mm.
73. The single integral compacted alumina sheet of any one of claims 66 to 70, having a thickness of about 100 mm to about 200 mm.
74. The single integral compacted alumina sheet of any one of claims 66 to 70, having a thickness of about 100 mm to about 150 mm.
75. The single integrally compacted alumina sheet of any one of claims 66 to 74 being binder-free.
76. Use of an alumina green body according to any one of claims 56 to 65 or a single integrally compacted alumina sheet according to any one of claims 66 to 75 in a single crystal growth process.
77. Use of an alumina green body according to any one of claims 56 to 65 or a single integrally compacted alumina sheet according to any one of claims 66 to 75 in a single crystal growth furnace.
78. Use of an alumina green body according to any one of claims 56 to 65 or a single integrally compacted alumina sheet according to any one of claims 66 to 75 in the production of sapphire.
Citation Information
Patent Citations
Manufacturing method of alumina pellet
KR1020130022616A